Animal cell culture : essential methods - Davis, John, 1952- (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2011)
Abstract: Animal cell culture is a widely used technology for producing recombinant proteins. The ability to make post-translational modifications and secrete the active forms of the protein into the culture medium represents major advantages over other processes. The growing market demand for pharmaceuticals has created a need for increased production capacity; however, achieving productivity gains in both the upstream stage and downstream processes can subject cells to aggressive environments such as those involving hydrodynamic stresses. Although numerous studies have explored the consequences of cell damage due to hydrodynamic stress, there has been a lack of understanding of the mechanism of such damage at a cellular level. Cell damage can also influence biomedical applications. Cells manipulated in instruments such as diagnosis and analysis devices can experience hydrodynamic forces.
The cell culture laboratory / Sue Clarke and Janette Dillon -- Sterilization / Peter L. Roberts -- Microscopy of living cells / Colin Gray and Daniel Zicha -- Basic techniques and media, the maintenance of cell lines, and safety / John M. Davis -- Development and optimization of serum- and protein-free culture media / Stephen F. Gorfien and David W. Jayme -- Cryopreservation and banking of cell lines / Glyn N. Stacey, Ross Hawkins and Roland A. Fleck -- Primary culture of specific cell types and the establishment of cell lines / Kee Woei Ng [and others] -- Cloning / John Clarke, Alison Porter and John M. Davis -- The quality control of animal cell lines and the prevention, detection and cure of contamination / Peter Thraves and Cathy Rowe -- Systems for cell culture scale-up / Jennifer Halsall and John M. Davis -- Good laboratory practice in the cell culture laboratory / Barbara Orton.
Includes bibliographical references and index.
Print version record.
Keywords: Cell culture -- Technique; Tissue culture -- Technique; SCIENCE -- Life Sciences -- Cell Biology; Cell culture -- Technique; Tissue culture -- Technique; Electronic books